2006
DOI: 10.1016/j.nima.2005.11.047
|View full text |Cite
|
Sign up to set email alerts
|

Charge identification of highly ionizing particles in desensitized nuclear emulsion using high speed read-out system

Abstract: Preprint submitted to Elsevier Science 1 November 2005 SLAC-PUB-11858We performed an experimental study of charge identification of heavy ions from helium to carbon having energy of about 290 MeV/u using an emulsion chamber.Emulsion was desensitized by means of forced fading (refreshing) to expand a dynamic range of response to highly charged particles. For the track reconstruction and charge identification, the fully automated high speed emulsion read-out system, which was originally developed for identifying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…The black tracks are easy to recognise visually since they are heavily ionising, they have short path lengths and stop within two lead plates. The separation between mip and grey tracks is based on the pulse height volume (PHV) [20,21] which is defined as the sum of the number of pixels associated with each track in all sixteen layers of images [22,23]. PHV indicates the track width and is therefore a measure of the grain density of a track that reflects the energy deposition of a particle in the emulsion film.…”
Section: Discussionmentioning
confidence: 99%
“…The black tracks are easy to recognise visually since they are heavily ionising, they have short path lengths and stop within two lead plates. The separation between mip and grey tracks is based on the pulse height volume (PHV) [20,21] which is defined as the sum of the number of pixels associated with each track in all sixteen layers of images [22,23]. PHV indicates the track width and is therefore a measure of the grain density of a track that reflects the energy deposition of a particle in the emulsion film.…”
Section: Discussionmentioning
confidence: 99%
“…In Ref. [18] we showed that charges of ion tracks can be identified up to Z = 6 with the refreshing method. Sheets-B and D were refreshed for three days under the temperatures of 40 • C and 38 • C respectively and the relative humidity of 98%.…”
Section: B Beam Exposure and Developmentmentioning
confidence: 99%
“…We conducted an experiment to study charge identification by refreshing method using HIMAC synchrotron and demonstrated that the charge of He, Li, Be, B and C, whose energies were around 290 MeV/u, were well discriminated [11]. Also this method was studied by using an emulsion scanning system developed in Italy [12].…”
Section: Charge Identification By Refreshing Methodsmentioning
confidence: 99%